Incorporating CsF into the PbI2 Film for Stable Mixed Cation‐Halide Perovskite Solar Cells. Issue 40 (17th September 2019) - Yi, Xiaohui; Zhang, Zhiming; Chang, Ailing; Mao, Yichen; Luan, Yigang; Lin, Tao; Wei, Yuanzhi; Zhang, Yanyan; Wang, Fuyi; Cao, Shaokui; Li, Cheng; Wang, Jizheng
Abstract: Adding a small amount of CsI into mixed cation‐halide perovskite film via a one‐step method has been demonstrated as an excellent strategy for high‐performance perovskite solar cells (PSCs). However, the one‐step method generally relies on an antisolvent washing process, which is hard to control and not suitable for fabricating large‐area devices. Here, CsF is employed and Cs is incorporated into perovskite film via a two‐step method. It is revealed that CsF can effectively diffuse into the PbI2 seed film, and drastically enhances perovskite crystallization, leading to high‐quality Cs‐doped perovskite film with a very long photoluminescence carrier lifetime (1413 ns), remarkable light stability, thermal stability, and humidity stability. The fabricated PSCs show power conversion efficiency (PCE) of over 21%, and they are highly thermally stable: in the aging test at 60 °C for 300 h, 96% of the original PCE remains. The CsF incorporation process provides a new avenue for stable high‐performance PSCs. Abstract : CsF is adopted to modify the PbI2 seed for highly crystallized Cs‐doped perovskite film with very long carrier lifetime, and very high light, thermal and humidity stabilities. As a result, the planar perovskite solar cells based on the Cs‐doped film also show very good stability with negligible hysteresis, and display PCEs of over 21%.